學科領導在課程改革中的角色：香港個案研究Roles of Department Heads in Curriculum Change: A Hong Kong Case Study - 譚彩鳳Choi-Fung Tam (Higher Education Foundation, 2007)
西方研究發現學科組織是學校改進的重要單位，學科領導對推動課程革新、 改善同儕的溝通及協作、重組組織結構等有不少貢獻。本個案研究旨在探索兩位中 文學科領導的角色、風格，並揭示在其領導下學科組織文化的特色。研究發現學科 領導具備多元化的角色，與其職責有密切關係。再者，這兩位領導的風格各有不 同，其中一位具有民主型的領導風格，給同事賦權增能，與他們共享決策權；另一 位卻具有支援性的領導風格，為學科組織成員樹立榜樣。研究揭示學科領導是促進 課程變革的重要人物，其開放態度有利新課程的實施。 Western studies reveal that subject department is an important changing unit for school improvement. Heads of departments contribute significantly to the changes of curriculum, improvement of communication and collaboration among colleagues, and restructuring of organizations. This case study aimed at investigating the roles and leadership styles of two Chinese Language department heads, and the characteristics of the departmental culture under their leadership. The results reported that the roles of department heads were multi-dimensional; which were closely related to their duties. Furthermore, the leadership styles of the two department heads were different. One of them exercised democratic leadership; power and decision-making were shared with her colleagues. While the other tended to perform supportive leadership, she was a role model for her members. The findings concluded that department heads played an important role in curriculum change and their openness facilitated the successful implementation of new curriculum.